Mobile Attendance Tracking System (MobATS) focuses on computerized reporting and notification / Muhammad Ikhsan Ahmad Roslan - Ahmad Roslan, Muhammad Ikhsan (2013)
The current system is inefficient and ineffective due to obsolescence and unreliability of the existing conventional attendance system. The existing system requires student to manually sign the attendance sheet whenever they attend classes. By using this conventional system many problems have occurred. This includes unwanted time being consumed by student to sign their attendance during class hours. In addition, some students who do not attend the class may ask their friends to sign the attendance for them. The main focus of this study is on students’ attendance registration using Access Point (AP) and student smartphone. The main objective of this system is to enable generate reports and to send warning notifications to students who has a bad record of attendance. In addition, by having online system and database it can help the lecturer to keep track of their students’ attendance. In the future, deploying the system throughout the faculty will benefit not only management but also students which could possibly be a key factor in improving teaching quality time and monitoring students’ performance. In this project, Rapid Application Development (RAD) methodology has been chosen as a software development methodology. Rapid Application Development will use minimal planning depending on the rapid prototype request and the lack of extensive preplanning will allow much faster and easier changes in the requirement later. Furthermore, it is flexible and adaptable to changes for the prototype later. In this project, it consist of six different phases which are analysis and quick design, build, demonstrate, refining, testing and lastly implementation. In conclusion the system can be easily accessed by the lecturer via the web page and a report can be generated in real time processing thus providing valuable information with regard to the students’ attendance.